2023
DOI: 10.1021/acs.inorgchem.2c02371
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy-Dependent Photocatalytic Selective Synthesis of an Unsaturated Amide on Spinel CuFe2O4

Abstract: Oxygen vacancies can change the physical and chemical properties of oxide semiconductors, which is applied to the field of ph otocatalysis, including water splitting, carbon dioxide reduction, and organic synthesis. However, the mechanism of oxygen vacancies in photocatalytic organic synthesis is still unclear. Herein, oxygen vacancies constructed on spinel CuFe 2 O 4 nanoparticles were found to trigger the photocatalytic synthesis of an unsaturated amide with high conversion and selectivity. Such superior per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Contributions at 530.2 and 531.2 eV could be distinguished after Gaussian fitting, which are attributed to the lattice oxygen (O L ) and (O V ), respectively. Observation of a higher proportion of O V area indicates an increased concentration of O V after PTR [48].…”
Section: Characterisation Of Oxygen Carriermentioning
confidence: 92%
See 1 more Smart Citation
“…Contributions at 530.2 and 531.2 eV could be distinguished after Gaussian fitting, which are attributed to the lattice oxygen (O L ) and (O V ), respectively. Observation of a higher proportion of O V area indicates an increased concentration of O V after PTR [48].…”
Section: Characterisation Of Oxygen Carriermentioning
confidence: 92%
“…The smaller the diameter of the circle, the higher the charge transfer rate that can be reached [47]. The reduced sample exhibited a smaller semicircle diameter than the fresh sample and cycled sample, corresponding to the enhanced charge transfer of photo-induced carriers due to the effects of V O s [48]. It could be found that the reduced sample (under illumination) showed the lowest interfacial electron transfer resistance; this confirmed that most V O s were produced in the reduced sample (under illumination).…”
Section: Characterisation Of Oxygen Carriermentioning
confidence: 98%
“…Transitional metal oxides are promising candidate catalysts in various catalytic reactions due to their storage abundance, component variety, variable oxidation states, high stability, and adjustable geometric/electronic structure. As one of the most studied transitional metal oxides, spinel Co 3 O 4 stands out owing to its good redox capability, facile oxygen mobility, and relatively weak Co–O bond strength. Partially substituting Co in the Co 3 O 4 lattice with a second metal is a common strategy to achieve the performance enhancement via synergistic catalysis when single Co 3 O 4 cannot meet all the requirements. Especially, well-defined bimetallic ACo 2 O 4 spinels (A = Ni, Cu, Mg, etc.…”
Section: Introductionmentioning
confidence: 99%